Effectiveness Of Head And Foot Massage Accompanied With Surah Ar-Rahman On Reducing Headache In Hypertension Patients At Proklamasi Hospital - Tri Mochartini; Evi Sulastri (Universitas Pahlawan Tuanku Tambusai, 2026)
Background : Hypertension is often accompanied by headaches due to impaired cerebral perfusion which not only causes discomfort but can also interfere with daily activities. Therefore , non-pharmacological approaches including safe and effective complementary therapies are important to research. One of the non-pharmacological approaches known to be effective in helping relieve pain is head massage and foot massage, which can improve circulation and stimulate the nervous system for relaxation, respectively. Psychospiritual therapies such as listening to Surah Ar-Rahman have been reported to reduce stress and help the body enter a state of relaxation, which in turn can contribute to reducing pain perception. Objective : This study aims to determine the effectiveness of head and foot massage accompanied by murottal Surah Ar-Rahman on reducing headaches in hypertensive patients. Method : Quasi-experimental design with a pretest–posttest control group involving 48 respondents (24 intervention, 24 control). Pain levels were measured using the Numeric Rating Scale (NRS). Results : Results showed a significant reduction in pain in the intervention group (p=0.001), while in the control group it was not significant (p=0.317). Conclusion : It was concluded that the combination of interventions was effective in reducing headaches